Simulation and evaluation of the performance of various sensor-sensing silicones to detect methane-soluble in fermentation process - Saeed Rahimi; soheil Rezazadeh Mofradnia; Fatemeh Yazdian; Behnam Rasekh; Seyedabas Shojasadati (مجله مدل سازی در مهندسی, 2019)
At present, spectrometric chromatography are used to methane in the fermentation process, but the use of off-line mass spectrometry requires the sampling and maintenance of the solution. Silicon membrane-based gas sensors are designed and used to detect methane based on this principle. The simulation of this sensor was carried out using COMSOL Multhiphysics (CM) 5.2 A software in 3D. Input gas helium was applied at three values of 40, 50 and 60 ml/min. Also, silicon tubes with lengths of 5, 10 and 15 cm and in three diameters of 0.05, 0.05, and 0.25 cm were investigated. The shortest response time from the sensor simulation is 10% compared to the results of the experimental at 1.6 minutes. The shear stresses, the effect of inlet gas velocity, flow pressure and fluid concentration in this study were compared. All result showed that the silicon membrane-based have been best absorbent for gas specially Methane.